Emerging therapies in the medical management of thyroid eye disease - Kamboj, Alisha; Harrison, Andrew R.; Mokhtarzadeh, Ali (Frontiers in Ophthalmology, 2023)
Introduction:Thyroid eye disease (TED) is an immune-mediated disorder associated with a heterogenous array of manifestations that may unfavorably impact vision and quality of life. As understanding of this entity's complex pathogenesis has evolved, so have therapies with novel molecular targets offering promise for improved patient outcomes. Methods:Mini review. Results:Emerging immunologic therapies for the management of thyroid eye disease have diverse mechanisms of actions and routes of administration. Different conventional and biological immunosuppressive agents have been studied as mediators of the autoimmune and autoinflammatory pathways in TED. Teprotumumab-an anti-IGF-1R monoclonal antibody that has recently emerged as a first-line therapy for active, moderate-to-severe TED-has demonstrated statistically significant improvements in proptosis, diplopia, clinical activity score, and quality of life compared to placebo. Currently under investigation are several other agents, with varying administration modalities, that aim to inhibit IGF-1R: VRDN-001, VRDN-002 or VRDN-003, lonigutamab, and linsitinib. Tocilizumab, a monoclonal antibody of interleukin-6, has played a role in the management of multiple autoimmune and inflammatory conditions and may offer promise in TED. Another incipient biologic target for TED management is the neonatal-Fc-receptor, inhibition of which has potential to decrease recycling of immunoglobulin and antibody levels; agents addressing this target including monoclonal antibodies as well as antibody fragments. Finally, hypolipidemic agents may play a role as mediators of TED-associated inflammation. Conclusion:Among the agents under investigation that aim to decrease ocular morbidity associated with TED are agents that IGF-1R, interleukin-6, and the neonatal-Fc-receptor. The management of TED continues to expand with novel immunologic approaches for disease therapy.